Why do we have sex? Reflections from a Stepping Stones participatory action research with youth LGBTI in Johannesburg - Nduna, M.; Kiguwa, P. (South African Journal of Higher Education, 2017)
Research on youth homosexuality is predominantly deficit model orientated. This research principally focuses on the impact of being different, low self-worth, distress, stigma, discrimination, HIV and so on. Data gathered through a series of Stepping Stones workshops conducted at a local University in Gauteng provided us with an opportunity to explore young lesbian, gay and bisexual men and women’s engagement with sex. The aim of this study was to understanding the relevance of Stepping Stones for the LGB community, inform about circumstances surrounding why LGB youth engage in sex and offer a comparison with research from heterosexual youth. The authors facilitated nine workshop sessions with twelve lesbian, gay and bisexual men and women aged 18-25 at the University using Stepping Stones. Data analysed was drawn from the session entitled ‘Why we behave as we do’. We used a thematic analytic approach to analyse the data. Some of the motivations for sex were in fact about the participants; they wanted to have sex. Off course others were about the partner; sex was engaged in to please the other. This study concludes that the reasons lesbian, gay and bisexual youth engage in sex may not be unique and thus they too need to be included in mainstream sexuality and safer sex interventions.